2014
DOI: 10.1007/s00701-014-2296-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of simple suturing and elevation debridement in compound depressed fractures with no significant mass effect

Abstract: Simple suturing seems to be an equally good option in patients with compound depressed fracture with no significant mass effect or brain matter herniation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
10
1
Order By: Relevance
“…9,18,20 Craniotomy and elevation of depressed fracture was done in 42% patients. Mukherjee et al 16 had done surgical elevation debridement in 21% patients which is lower than this study whereas study by Braakman 9 who has done surgical intervention in 73 % patients and study by Hossain et al 20 who has performed surgical treatment in 72% patients, which is higher than this study. Highest rate of Dural tear was seen in the compound type depressed fracture than simple type in this study, which is consistent with the study by Steinbok et al 19 In this study, we have observed infection rate of 2%.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…9,18,20 Craniotomy and elevation of depressed fracture was done in 42% patients. Mukherjee et al 16 had done surgical elevation debridement in 21% patients which is lower than this study whereas study by Braakman 9 who has done surgical intervention in 73 % patients and study by Hossain et al 20 who has performed surgical treatment in 72% patients, which is higher than this study. Highest rate of Dural tear was seen in the compound type depressed fracture than simple type in this study, which is consistent with the study by Steinbok et al 19 In this study, we have observed infection rate of 2%.…”
Section: Discussioncontrasting
confidence: 62%
“…9,16,17 This study revealed early epilepsy in 4 % versus late epilepsy in 2% of the patients. Al-Haddad et al 17 reported early epilepsy of 12.3% versus late epilepsy of 6.9%, Jennett et al 10 found early epilepsy of 10 % versus late epilepsy of 15% and Mukherjee et al 16 has mentioned late epilepsy of 3.7% versus 0% in simple suturing and elevation debridement group respectively. Focal deficit was observed in 8 % patients in this study.…”
Section: Discussionmentioning
confidence: 82%
“…17,37 However, the burden experienced by the caregivers of TBI or other neurological illnesses may be higher in developing countries like India due to the poor support system, inadequate use of hospital services, home care strategies, and rehabilitation facilities. 38,39 Our study also has found an adverse impact of the cognitive-behavioral and functional impairment of the TBI survivors on caregiver burden. Managing patients with behavioral symptoms such as anxiety, depression, and irritability is a stress-inducing task for the caregivers.…”
Section: Discussionmentioning
confidence: 55%
“…Similar male preponderance is noted in other studies too. 8,11 RTA was most common cause of depressed fracture (50%). However, some other studies implicate fall as the most common mode of injury.…”
Section: Discussionmentioning
confidence: 99%